ORGANIZATIONAL CULTURE AND WORK MOTIVATION AT PT. TELKOM WITEL MAGELANG: (Case Study at the Consumer Service Unit of PT. Telkom Witel Magelang) - Nilna Amalia Marhamah; Khairul Ikhwan (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study aimed to assess the organizational culture and employee motivation at PT. Telkom Witel Magelang (Study Case in Consumer Service units). This study is carried out by quantitative methodology and a descriptive analysis. The sampling method used in this study is a sample of roughly 40 active consumer service units, which also constitute the population. The method being used is a method of conducting surveys using questionnaires and observation. The technique for data analysis being used is likert scale analysis with SPSS. According to analysis that has already been done, there is a 0.372-point correlation between the variables organizational culture and work motivation. Organizational culture has no significant effect on employee performance, while work motivation has an effect on employee performance. The influence of organizational culture on employee performance is as large as the variable Organizational Culture (X1) and Motivation (X2) simultaneously has an effect on the Performance variable (Y) by 37.2%. While the remaining 62.8% is influenced by other variables beyond this study.